Rainfall characteristics and probability analysis of dryand wet-spells for crop planning in Dhanora block, Seoni, Madhya Pradesh - DASH, BENUKANTHA; NAGARAJU, M.S.S.; TIWARI, GOPAL; SAHU, NISHA; JANGIR, ABHISHEK; SRIVASTAVA, RAJEEV; SINGH, S. K. (Journal of Soil and Water Conservation, 2020)
Understanding the probable period of onset and withdrawal of monsoon, amount of rainfall and its distribution over a cropping season is pre-requisite to timely agricultural operations, selection of crop varieties and cropping pattern in a region. Dhanora block is one of the eight blocks of Seoni district with undulating landform, erratic rainfall and mainly rainfed farming with less irrigated area (22.02%). The mean annual rainfall of the study area is 1197.7 mm. Rainfall received during South West monsoon period (June-September) is 1035.9 mm which accounts for 86.5% of total rainfall, whereas, post-monsoon (October- January) and pre-monsoon (February- May) accounts for 7.5 and 6%, respectively. The mean monsoon period is 15-week long (105 days) with mean onset of monsoon on 25th standard meteorological week (SMW) and mean withdrawal on 40th SMW. Here, Markov chain model used for dry and wet spell analysis for weekly rainfall. If total amount of any week of rainfall is equal or more than 10 mm, 20 mm and 40 mm, it considered as wet weeks and less than this considered as dry weeks. Probability of two or three consecutive dry weeks at 20.00 mm rainfall is less than 40% during 25th SMW to 39th SMW and more than 50% from 1st to 23rd SMW and 40th SMW to 52nd SMW. Probability of two and three consecutive wet weeks at 20 mm rainfall is more than 50% from 25th SMW to 36th SMW and 27thSMW to 36th SMW, respectively. Based on probability analysis of rainfall and moisture availability, various water management and crop planning strategies have been discussed in this paper for Dhanora block, Seoni